Fictional world and effective real world in José Saramago’s "La balsa de piedra" - Rodríguez Pequeño, Mercedes (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
This brief artide refers to the semantic features of the literary referent. In the annalysis and in the interpretation of this narrative work is used the method furnished by the "Possible Worlds Theory" which sets that the esthetic success as well as the fictionality in La balsa de piedra have been achieved through the attentive counterbalance of the three types of worlds: real world, probable fictional world, and non-probable fictional world.